Financial development - economic growth nexus in Pakistan: New evidence from the Markov switching model - Abdul Rahman; Muhammad Arshad Khan; Lanouar Charfeddine (Cogent Economics & Finance, 2020)
This paper investigates the impact of financial development on economic growth in Pakistan using the Markov Switching Model over the period 1980-2017. The results based on two-state Markov switching model confirm the Schumpeter's view that finance spurs growth. The result reveals that financial development augments economic growth in both high and low economic growth regimes in Pakistan. However, the impact of financial development on economic growth is found to be relatively higher in the high-growth regime. This implies that economic growth responds differently to financial development in low-growth and high-growth regimes. Among the control variables, trade openness and government expenditures impact economic growth positively, while labour force exerts a negative impact on economic growth.
Keywords: C24; F43; O43; 330; Financial development; ﻿ economic growth; ﻿ regime switching model; high- and low-growth regime; Pakistan